Pengembangan Bahan Ajar Berbasis Pendekatan Content and Language Integrated Learning (CLIL) pada Pembelajaran Menulis Puisi Siswa Kelas IV SDN 86 Kaur - Ahmad Fadilah; Abdul Muktadir; Puspa Djuwita (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2023)
The development research model used is the Borg and Gall model. The instruments in this study were documentation, interviews, teacher and student response questionnaire validation sheets. Based on the results of research and development, it can be concluded that the teaching materials developed are valid and feasible to use. The average aspect of the presentation of the analysis obtained an Aiken's V coefficient with a score of 0.98, with the criteria of "very valid". The results of the expert validation are in the "very feasible" criteria. Teaching materials are developed for use by teachers in teaching and well used by students in learning. This is shown by the results of the teacher's response analysis with an average score of 99.6% in the "very good" criterion. From the analysis of student responses, an average score of 99.65 was in the "very good" criteria.